EVALUASI PELAKSANAAN KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN SEJARAH: STUDI KASUS DI SMAN 1 SUKOHARJO - Frido Septiansyah; Leo Agung Sutimin (Empowerment Journal, 2026)
This study aims to analyze history teachers' understanding of the concepts and principles of the Independent Curriculum at SMAN 1 Sukoharjo, identify learning implementation, and examine barriers to its implementation. The study used a descriptive qualitative approach with a case study design. Data were collected through learning observations, interviews with the vice principal for curriculum, history teachers, and students, and analysis of teaching module documents. Informants were selected using purposive sampling, data validity was tested through source triangulation, and analysis was conducted interactively. The results showed that teachers had a good understanding of the independent curriculum as a flexible, student-centered curriculum that encourages critical thinking. Learning implementation took place actively through discussions and presentations, as well as the use of a variety of assessments. Measurably, approximately 70% of learning activities reflected the principles of active learning. However, the utilization of assessment results for further learning planning was not optimal. Obstacles encountered included adapting teaching modules, time constraints, discussion management, and differences in students' analytical abilities. The impact was suboptimal differentiated learning and continuous assessment cycles. In conclusion, the implementation of the Independent Curriculum has gone well, but it needs to be strengthened in the use of assessment and learning management to make it more effective and sustainable.